Heart failure with preserved ejection fraction (HFpEF) pathophysiology study (IDENTIFY-HF): does increased arterial stiffness associate with HFpEF, in addition to ageing and vascular effects of comorbidities? Rationale and design - Prithwish Banerjee; Gordon McGregor; Richard Powell; Francesco P Cappuccio; Danish Ali; Nualla Callan; Stuart Ennis; Scott McGuire; Martin O Weickert; Michelle A Miller (BMJ Open)
Aims There has been a paradigm shift proposing that comorbidities are a major contributor towards the heart failure with preserved ejection fraction (HFpEF) syndrome. Furthermore, HFpEF patients have abnormal macrovascular and microvascular function, which may significantly contribute towards altered ventricular-vascular coupling in these patients. The IDENTIFY-HF study will investigate whether gradually increased arterial stiffness (in addition to ageing) as a result of increasing common comorbidities, such as hypertension and diabetes, is associated with HFpEF.Methods and analysis In our observational study, arterial compliance and microvascular function will be assessed in five groups (Groups A to E) of age, sex and body mass index matched subjects (age ≥70 years in all groups):Group A; normal healthy volunteers without major comorbidities such as hypertension and diabetes mellitus (control). Group B; patients with hypertension without diabetes mellitus or heart failure (HF). Group C; patients with hypertension and diabetes mellitus without HF. Group D; patients with HFpEF. Group E; patients with heart failure and reduced ejection fraction (parallel group). Vascular function and arterial compliance will be assessed using pulse wave velocity, as the primary outcome measure. Further outcome measures include cutaneous laser Doppler flowmetry as a measure of endothelial function, transthoracic echocardiography and exercise tolerance measures. Biomarkers include NT-proBNP, high-sensitivity troponin T, as well as serum galectin-3 as a marker of fibrosis.Ethics and dissemination The study was approved by the regional research ethics committee (REC), West Midland and Black Country 17/WM/0039, UK, and permission to conduct the study in the hospital was also obtained from the RDI, UHCW NHS Trust. The results will be published in peer-reviewed journals and presented in local, national and international medical society meetings.Trial registration number NCT03186833